2021
DOI: 10.1007/s10648-021-09618-5
|View full text |Cite
|
Sign up to set email alerts
|

Math Performance and Academic Anxiety Forms, from Sociodemographic to Cognitive Aspects: a Meta-analysis on 906,311 Participants

Abstract: The relationship between anxiety and mathematics has often been investigated in the literature. Different forms of anxiety have been evaluated, with math anxiety (MA) and test anxiety (TA) consistently being associated with various aspects of mathematics. In this meta-analysis, we have evaluated the impact of these forms of anxiety, distinguishing between different types of mathematical tasks. In investigating this relationship, we have also included potential moderators, such as age, gender, working memory, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 243 publications
(161 reference statements)
5
104
3
2
Order By: Relevance
“…Thus, the mathematics performance measures seemed to be relatively independent of working memory (though this did correlate with Arithmetic scaled score), test anxiety, and even of one another. This differs somewhat from the findings of some other studies, which found stronger influences on mathematical performance of test anxiety (Devine et al, 2012) of working memory (Skagerlund et al, 2019;Caviola et al, 2021) and especially of mathematics anxiety (Ma and Kishor, 1997;Dulaney et al, 2017;Skagerlund et al, 2019;Zhang et al, 2019;Barroso et al, 2021;Caviola et al, 2021). The findings here probably correspond most to those of Douglas and LeFevre (2018), who found relatively limited influence of working memory on other factors and their interrelationships.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the mathematics performance measures seemed to be relatively independent of working memory (though this did correlate with Arithmetic scaled score), test anxiety, and even of one another. This differs somewhat from the findings of some other studies, which found stronger influences on mathematical performance of test anxiety (Devine et al, 2012) of working memory (Skagerlund et al, 2019;Caviola et al, 2021) and especially of mathematics anxiety (Ma and Kishor, 1997;Dulaney et al, 2017;Skagerlund et al, 2019;Zhang et al, 2019;Barroso et al, 2021;Caviola et al, 2021). The findings here probably correspond most to those of Douglas and LeFevre (2018), who found relatively limited influence of working memory on other factors and their interrelationships.…”
Section: Discussioncontrasting
confidence: 99%
“…Note that in contrast to a small number of studies [ 64 , 65 , 66 ], we did not find differences in the math anxiety–performance link with various aspects of math (calculation and fluency). More research is needed to comprehensively test these relations [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that state (or state-like) math anxiety, e.g., [ 6 , 44 , 57 , 58 , 59 ] is more associated with math performance than trait math anxiety, e.g., [ 40 , 58 , 60 , 61 , 62 , 63 ], and the link between math anxiety and math performance is stronger in more complex math tests [ 64 , 65 , 66 ]. However, only a small number of studies used multiple measures of math performance [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, videos could be a simple and effective way to develop and disseminate training interventions on a large scale, given the popularity and accessibility of video streaming platforms among preschoolers [ 67 , 68 , 94 ]. They could be used to deliver entertaining, targeted and effective interventions in deprived settings where numerical skills are undertrained, and thereby prevent the risk of children developing difficulties and negative attitudes to mathematics as they grow older [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%